2021
DOI: 10.1186/s12887-021-02518-1
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia, sex and miscarriage history may influence the association between cesarean delivery and autism spectrum disorder

Abstract: Background To explore the association between cesarean section (CS) and risk of autism spectrum disorder (ASD), and evaluate the possible factors influencing this association. Methods In total, 950 patients diagnosed with ASD and 764 healthy controls were recruited in this study. Socio-demographic characteristics and prenatal, perinatal, and neonatal characteristics were compared between the two groups. Univariate and multivariable conditional logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…After adjustment for potential confounding factors, the risk of ASD was 38% higher in children born by CS than in those born by vaginal delivery in this study. In the literature, there are conflicting reports regarding the association between CS and ASD [ 7 , 10 , 11 , 17 ]. Previous studies and a meta-analysis indicated that CS increased the risk of ASD [ 7 , 11 , 17 ], which is line with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After adjustment for potential confounding factors, the risk of ASD was 38% higher in children born by CS than in those born by vaginal delivery in this study. In the literature, there are conflicting reports regarding the association between CS and ASD [ 7 , 10 , 11 , 17 ]. Previous studies and a meta-analysis indicated that CS increased the risk of ASD [ 7 , 11 , 17 ], which is line with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a meta-analysis including 13 studies, CS birth was linked to a greater risk of future ASD (odds ratio (OR) 1.23) than vaginal birth [ 11 ]. Although ASD is a highly inheritable disorder with male preponderance, relevant environmental factors may be sex-specific [ 9 ]; for example, the indications for CS and the anesthesia method used during CS were found to have some effects on ASD morbidity depending on the infants’ sex [ 8 , 17 , 18 ]. Some environmental factors in the perinatal period may also be involved in ASD morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that the within-pair analysis suggested that anesthesia exposure was associated with a higher ADHD score [24] and the later ADHD are associated with prolonged or multiple exposure to anaesthetics [25]. Fortunately, some studies have concluded that children receiving anesthesia in utero [26], in their first 2 years life or later, are not more likely to develop ASD [27]. In addition, an international, multicenter, randomized, controlled equivalence trial has strongly evidenced that an hour of GA in early infancy does not change neurodevelopmental outcome and behavioral measures compared to awake-regional anaesthesia [28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 13 studies were included in this meta-analysis (Figure 1). Seven studies 10,11,13,15,[18][19][20] had a case-control design, four 12,14,21,22) had a cohort design, and two 23,24) had a crosssectional design. Among the included studies, seven were performed in Europe, four in the Americas, and one each in Africa and Europe.…”
Section: Description Of Studiesmentioning
confidence: 99%